Influence of lithium amount on vitreous enamel properties - Erayvaz, Ahmet Murat; Derun, Emek Moroydor (EDP SCIENCES S A, 2021)
Lithium is the lightest of all metals and the third element in the periodic table. Recent years, lithium salts have become an important input for the energy industry. Lithium carbonate and hydroxides are the basic building blocks of Li-ion battery production. The usage areas of lithium compounds are not limited to only energy; they are also utilized in heavy-duty machines, in the aluminum industry, in nuclear power plants and for glass, ceramics, frit, and coatings in industrial sectors. Lithium has also been found to be very useful in the development of harder, smoother, and more resistant low-temperature glasses, glazes, and enamels. It is also used in very-low-melting-point vitreous compositions like aluminum enamels, colors, fluxes, and glass-seals. The use of lithium also helps in the development of low-expansion bodies, glazes, and glasses. In this study, it is intended to explore the adherence forces in the steel sheet application of different amounts of lithium in enamel frit composition and to examine surface characteristics such as ease of cleaning, gloss, and color. For chemical characterization, X-ray fluorescence (XRF) spectrometry and color measurements were done with a Minolta CM-700d spectrometer device. Bond adherence tests were performed in accordance with the TS EN 10209 standard.
Keywords: Metallurgy & Metallurgical Engineering